An Effective Sodium-Dependent Glucose Transporter 2 Inhibition, Canagliflozin, Prevents Development of Hypertensive Heart Failure in Dahl Salt-Sensitive Rats - He, Lili; Ma, Sai; Zuo, Qingjuan; Zhang, Guorui; Wang, Zhongli; Zhang, Tingting; Zhai, Jianlong; Guo, Yifang (Frontiers in Pharmacology, 2022)
Background: To investigate the protective effect of Canagliflozin (CANA) on myocardial metabolism and heart under stress overload, and further to explore its possible molecular mechanism. Methods: High-salt diet was used to induce heart failure with preserved ejection fraction (HFpEF) and then the physical and physiological indicators were measured. Cardiac function was evaluated by echocardiography and related indicators. Masson trichrome staining, wheat germ agglutinin and Immunohistochemical staining were conducted for histology analysis. Meanwhile, oxidative stress and cardiac ATP production were also determined. PCR and western blotting were used for quantitative detection of related genes and proteins. Comprehensive metabolomics and proteomics were for metabolic analysis and protein expression analysis. Results: In this study, CANA showed diuretic, hypotensive, weight loss, and increased intake of food and water. Dahl salt-sensitive (DSS) rats fed with a diet containing 8% NaCl AIN-76A developed left ventricular remodeling and diastolic dysfunction caused by hypertension. After CANA treatment, cardiac hypertrophy and fibrosis were reduced, and left ventricular diastolic function was improved. Metabolomics and proteomics data confirmed that CANA reduced myocardial glucose metabolism and increased fatty acid metabolism and ketogenesis in DSS rats, normalizing myocardial metabolism and reducing myocardial oxidative stress. Mechanistically, CANA up-regulated p-adenosine 5'-monophosphate-activated protein kinase (p-AMPK) and sirtuin 1 (SIRT1), and significantly induced the expression of peroxisome proliferator-activated receptor gamma coactivator-1 alpha (PGC-1a). Conclusions: CANA can improve myocardial hypertrophy, fibrosis and left ventricular diastolic dysfunction induced by hypertension in DSS rats, possibly through the activation of AMPK/SIRT1/PGC-1a pathway to regulate energy metabolism and oxidative stress.